2019
DOI: 10.1097/bpo.0000000000000923
|View full text |Cite
|
Sign up to set email alerts
|

Open Surgical Release of Posttraumatic Elbow Contracture in Children and Adolescents

Abstract: Background: Post-traumatic elbow contractures in children and adolescents are challenging to manage, and studies investigating surgical treatment are limited by the rarity of this condition. Small case series have shown variable gains in immediate and long-term elbow arc of motion after open surgical release. We reviewed our experience with open surgical release of post-traumatic elbow contracture in patients less than 21 years old at two institutions. Methods: A retrospective chart review identified patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…This finding was consistent with the outcomes of the latest literature. Piper et al 9 studied 26 young patients and reported a similar increase of 49 degrees. Though the difference in pathologic condition and surgical solution makes the improvement different, here we used different approaches as a whole adapting to pathologic conditions and study the relationship between surgical methods and improvement according to the postoperative baseline in treating the stiff elbow.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…This finding was consistent with the outcomes of the latest literature. Piper et al 9 studied 26 young patients and reported a similar increase of 49 degrees. Though the difference in pathologic condition and surgical solution makes the improvement different, here we used different approaches as a whole adapting to pathologic conditions and study the relationship between surgical methods and improvement according to the postoperative baseline in treating the stiff elbow.…”
Section: Discussionmentioning
confidence: 81%
“… 20 A decreased ROM in the elbow has significantly interfered with qualities of daily living in children and adolescents. 9 , 12 Several studies have investigated the management of adult posttraumatic elbow contractures, with satisfactory outcomes of open elbow release. 1 , 6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations